AB0575 Ocular Findings in Takayasu's Arteritis is Milder in A Turkish Series. (10th June 2014) - Esen, F.; Kazokoglu, H.; Alibaz-Oner, F.; Celik, G.; Direskeneli, H.
Abstract : Background: Takayasu's arteritis (TAK) is an inflammatory, granulomatous vasculitis affecting aorta and its major branches. According to the type of vascular involvement, Takayasu's retinopathy (TR) and hypertensive retinopathy (HR) may be observed. Complications related to chronic immunosuppression and steroid therapy are also not infrequent in TAK and complications including amarosis fugax, iris neovascularization, glaucoma, cataract, uveitis and anterior ischemic optic neuropathy have been reported. Methods: We screened 46 patients with TAK (43 female, 3 male, mean age 42.5±11.3 years, mean disease duration 5.7±5.1 years), followed at Marmara University Hospital Rheumatology clinics, for the presence of ocular complications. Forty patients were on low-dose (<10 mg/d prednisolone) corticosteroids, 25 were on azathioprine, 17 were on methotrexate and 2 patients were on leflunomide. Results: None of the patients suffered from an ocular disease activity or complication causing permanent reduction in visual acuity. Eight patients (17%) had HR (grade 1-2) and only one patient (2%) had TR (grade 1). Seven patients (15%) had posterior subcapsular cataract, one patient (2%) was bilaterally pseudophacic and 37 (83%) had no steroid-related cataract. None of the patients had steroid-induced glaucoma or neovascular glaucoma. When comparing the patients with or without cataract, there were no statistically significant differences for the cumulative steroid dose (7608±5954mg vs. 8746±5497mg; p=0.46) or ITAS scores for disease activity (6.7±1.5 vs. 9.4±5.4; p=0.28). The patients with HR had a higher disease duration compared to the patients without HR (8.4±6.9 years vs. 4.0±2.6 years; p=0.02) Conclusions: The prevalence of TR was reported to be higher (15% and 13.5%) 1–2 in previous two similar decriptive studies, while prevalence of HR (16% and 30.8%) 1–2 and steroid-related cataract (%23) 1 was similar to our study. We did not observe any of the other above-mentioned serious complications reported in the previous studies. This is the first study to report a low prevalence of TR and related ischemic complications in TAK. This finding can be explained by: 1. our unselected study population from a rheumatology clinic, rather than an ophthalmology clinic (usually with a selection bias), 2. our study group having a milder eye disease due to a sufficient control of general disease activity, attenuating the severity of ocular disease or 3. a milder clinical course of TAK in Turkey. Further follow-up of our cohort will clarify our observations better. References: Peter J, David S, Danda D, Peter JV, Horo S, Joseph G. Ocular manifestations of Takayasu arteritis: a cross-sectional study. Retina. 2011 Jun;31(6):1170-8 Chun YS, Park SJ, Park IK, Chung H, Lee J. The clinical and ocular manifestations of Takayasu arteritis. Retina. 2001;21(2):132-40. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2691